Pelatihan Pembuatan Sabun Mandi Kombucha Bunga Telang Kepada Mahasiswa Farmasi Pada Mata Kuliah Bioteknologi - Firman Rezaldi; Nurullah Asep Abdilah; Mu’jijah Mu’jijah; Fernanda Desmak Pertiwi; M. Fariz Fadillah; Usman Setiawan; Heny Sasmita; Ucu Wandi Somantri (Jurnal Pengabdian Pada Masyarakat Indonesia, 2022)
TRAINING ON MAKING TELANG FLOWER KOMBUCHA FERMENTED SOAP AS RAW MATERIAL FOR HALAL AND ENVIRONMENTALLY FRIENDLY COSMETICS FOR 5TH SEMESTER PHARMACY STUDENTS IN AN EFFORT TO IMPROVE CONVENTIONAL PHARMACEUTICAL BIOTECHNOLOGY SKILLS. The efficacy of kombucha as antibacterial, antioxidant, and anticancer is very open to opportunities to be developed as raw materials for drugs and cosmetics that are environmentally friendly and halal in the perspective of biotechnology. The purpose of this training is to provide the latest insight for 5th semester pharmacy students regarding the potential of telang flower kombucha as a raw material for halal and environmentally friendly cosmetics, thereby increasing conventional pharmaceutical biotechnology skills. The methods used are Preparation of the Training Place, Filling in Attendance List of Participants and Questionnaires, Opening of Training Events, and Implementation and Training of Making Telang Flower Kombucha Fermented Soap. Based on the results of both training activities carried out in classes A, B, D, and E, 5th semester Pharmacy Students, Faculty of Health Pharmacy, Mathla'ul Anwar University, Banten regarding Training on Making Fermented Soap Kombucha Telang Flowers as Raw Material for Halal and Environmentally Friendly Cosmetics to Pharmacy Students Smester 5 In an Effort to Improve Conventional Pharmaceutical Biotechnology Skills, the majority of students do not know much about the potential of kombucha fermentation of telang flower which has potential as a raw material for halal and environmentally friendly cosmetics. This is because they are more familiar with fermented kombucha as a functional drink, cosmetic raw materials from fermented kombucha in the form of bar soap and facial toner.